Black mass: Apocalyptic religion and the death of Utopia - John Gray; GRAY (John) (London Penguin Books, 2008)
A prophetic warning against the foolishness of crusades, John Gray's "Black Mass" challenges our belief in human progress. Our conventional view of history is wrong. It is founded on a pernicious myth of an achievable utopia that in the last century alone caused the murder of tens of millions. In "Black Mass" John Gray tears down the religious, political and secular beliefs that we insist are fundamental to the human project, examines the interaction of terrorism, declining world resources, environmental change, human myths of redemption and a flawed belief in Western democracy and shows us how a misplaced faith in our ability to improve the world has actually made it far worse. "Brilliant, frightening, devastating". (John Banville, "Guardian"). "A brilliant polemic...Gray's most powerful argument yet". (J.G. Ballard, "Guardian", Books of the Year). "Causes vertigo when it does not cause outrage". ("Sunday Times"). "Exhilarating, invigorating". ("Literary Review"). "Savage. Gray raises profound and valid doubts about the conventional "plot" of modern history". ("Financial Times"). "A load of bollocks ...could hardly be more bonkers if it was crawling with lizards".("Sunday Telegraph"). John Gray has been Professor of Politics at Oxford University, Visiting Professor at Harvard and Yale and Professor of European Thought at the London School of Economics. His books include "False Dawn: The Delusions of Global Capitalism", "Straw Dogs: Thoughts on Humans and Other Animals" and "The Immortalization Commission: The Strange Quest to Cheat Death". His selected writings, "Gray's Anatomy", was published in 2009.
Keywords: Terror in the Twentieth Century; Utopia Enters the Mainstream; Armed Missionaries; Americanization of the Apocalypse